Development of 28 GHz and 77 GHz, mega-watt gyrotrons for fusion devices - Kariya, T; Minami, R; Imai, T; Ota, M; Endo, Y; Kubo, S; Shimozuma, T; Takahashi, H; Yoshimura, Y; Ito, S; Mutoh, T; Sakamoto, K; et al. (2011)
A 28 GHz 1 MW with TE 8,3 cavity for GAMMA10 tandem mirror and a 77 GHz 1.5 MW gyrotron with TE 18,6 for Large Helical Device (LHD) have been developed to upgrade their Electron Cyclotron Heating (ECH) systems. In the 28 GHz gyrotron, the maximum power of 1.05 MW was obtained, which is in agreement with its design target value. And the high efficiency of 40% without collector potential depression (CPD) was obtained with 0.8 MW. In the first and second 77 GHz gyrotrons, 0.8 MW 3.6 sec., 0.3 MW 60 sec operations have been achieved, but several issues due to the stray RF and velocity dispersion have been found, too. In consideration of these, the design improvement was performed to aim at 1.5 MW in the third tube. In the short pulse test, the maximum output power of 1.6 MW and the maximum total efficiency of 49.4% with CPD were obtained. In the long pulse test, the pulse length extended to 5 sec with 1 MW, 1800 sec with 0.1 MW, 1.6 sec with 1.5 MW. Total injection power of 3.1 MW to LHD plasma has been achieved. It is shown that the electron beam pitch factor α decreases with increasing of beam current, comparing with the experimental and calculation results. © 2010 Springer Science+Business Media, LLC.